Celebrating traditional medical practice in the Shona novel Ndoitawo Zvakaita Vamwe. Issue 2 (3rd July 2019) - Chigidi, Willie; Charamba, Tyanai
Abstract : This article attempts to make a critical appraisal of PHD Ngwaraingwe's novel, Ndoitawo Zvakaita Vamwe . This novel was published in 1984, a few years into Zimbabwe's independence, but both the author and his work are little known by readers in the country. The purpose of this article, therefore, is to unravel Ngwaraingwe's artistic and creative purpose in writing this novel and perhaps draw readers' and critics' attention to it. The article makes the assertion that Ngwaraingwe aimed at making his contribution to the cultural revival that characterised the early years of independence in Zimbabwe. Guided by Afrocentricity, the writers of this article argue that Ndoitawo Zvakaita Vamwe is an attempt by Ngwaraingwe at propping up Shona traditional medicine and its practitioners by riding on the crest of the euphoric and celebratory mood that dominated the early post-independence years in Zimbabwe. Ngwaraingwe employs the oral narrative technique, and takes an ideological position to make a strong bid in favour of recognising Shona cultural institutions in national development . However, his bid to persuade the reader to buy into his project fails due to the introduction of fantastic elements and the use of sickening and unpleasant language.